Effectiveness of the Siddha Drug Maantha Kiyaalam on Neer Kana Maantham (Acute Naso Pharyngitis) – a Clinical Study - Susila.R; Esaivani.S; Kavitha.T; Usha.A (International Journal of Pharma and Bio Sciences, 2020)
Psoriasis is a hyperproliferative inflammatory noncommunicable skin disease. Though it has an unclear etiology, it has been proposed to be caused due to an interplay between a genetic predisposition and environmental factors (triggers) such as injury, infection, allergy, extremes of temperature, chemicals or stress. According to 2016 WHO report, the worldwide prevalence of psoriasis ranges between 0.09% and 11.4% among which Guttate Psoriasis occurs between 0.6 to 20% of individuals making it a serious global problem. . Around 13% psoriatic cases have been reported in Siddha central research Institute (SCRI), Chennai during 2016-17. Conventional medicine uses several medications such as non-steroidal anti-inflammatory drugs to treat psoriatic arthritis. But these medications are not free from their side effects. The literature of one among the Indian traditional system of medicine known as Siddha coins the terminology Kaalanjagapadai (ICD-S3) that can be well correlated with Psoriasis. This case report represents a 34 year old male psoriatic patient who was admitted in the Inpatient department (IPD) of Siddha central research institute (SCRI). The Siddha system emphasize the root cause of Psoriasis (Kalaanjagapadai) and all skin diseases as aggravated Vatham in its text Noi Naadal as “Vaatham allaathu meni kedathu.’’ Hence the treatment was initiated with Bethi maruthuvam Meganaatha kuligai - 260mg (Therapeutic purgation) for the first three days to alleviate Vatham followed by Parangipattai churnam 1gm, Palagarai parpam 100mg twice a day with milk after food. Vetpalai thylam 90ml/day and Vangaviranakalimbu 10 gms/day were used externally for 40 days. The clinical efficacy was assessed on Day-0 (Before treatment), Day-3 (After Purgation) and Day 40 (After medications) through specific tools such as Psoriasis area severity index score(PASI) , Insomnia severity index, Gastrointestinal symptom rating scale and Universal Pain assessment scale. The results showed significant reduction of PASI score from 46 to 1.9 and improvement in all other symptoms following Siddha treatment methods.